The Effect of Individual, Psychological, and Organizational Factors on Nurse Performance at H. Abdurrahman Sayoeti Hospital, Jambi City in 2024 - Misno Yulianto; Rumita Ena Sari; Hubaybah Hubaybah (PT. Anagata Sembagi Education, 2024)
The performance of nurses at RSUD H. Abdurrahman Sayoeti Jambi City is still not optimal. Based on nurse performance recapitulation data from January to December 2023, the achievement of nurse performance has not been maximally realised, with the expected target being 100% of nurses having excellent performance, but in reality it has not been achieved. This decline in performance can affect the level of patient and family satisfaction, as well as the quality of hospital services. This study aims to analyse the influence of individual, psychological, and organisational factors on nurse performance at H. Abdurrahman Sayoeti Hospital, Jambi City in 2024. This study used a quantitative method with a Cross Sectional design and involved 33 nurses selected using the Total Sampling technique. The results showed that factors such as tenure, attitude, motivation, leadership, and rewards had a significant relationship with nurses' performance, while age and gender showed no significant relationship. Of all the factors, motivation is the most dominant factor affecting nurses' performance. Therefore, it is important for hospitals to pay attention to strengthening nurses‘ motivation and positive attitude through the development of supportive programmes, such as more structured training and rewards, as well as effective leadership, to ensure nurses’ performance can be continuously improved in line with better service quality.